Influence of global and local features on parallel object identification - Šoliūnas, Alvydas (F1000 research, 2018)
Background: The present study concerns parallel and serial processing of visual information, or more specifically, whether visual objects are identified successively or simultaneously in multiple object stimulus. Some findings in scene perception demonstrate the potential parallel processing of different sources of information in a stimulus; however, more extensive investigation is needed. Methods: We presented one, two or three visual objects of different categories for 100 ms and afterwards asked subjects whether a specified category was present in the stimulus. We varied the number of objects, the number of categories and the type of object shape distortion (distortion of either global or local features). Results: The response time and accuracy data corresponded to data from a previous experiment, which demonstrated that performance efficiency mostly depends on the number of categories but not on the number of objects. Two and three objects of the same category were identified with the same accuracy and the same response time, but two objects were identified faster and more accurately than three objects if they belonged to different categories. Distortion type did not affect the pattern of performance. Conclusions: The findings suggest the idea that objects of the same category can be identified simultaneously and that identification involves both local and global features.